Corrosion properties of galvanic Fe–Mo(W), Fe–Mo–W coatings - Ved, M. V.; Sakhnenko, N. D.; Karakurkchi, A. V.; Pershina, K. D.; Yermolenko, I. Yu. (Науково-технологічний комплекс "Інститут монокристалів", 2019)
The methods of analysis of polarization dependences, the electrode impedance spectroscopy and gravimetry were used for the investigation of the corrosion properties of galvanic binary Fe–Mo(W) and ternary Fe–Mo–W coatings in the media of a different acidity. It was shown that the corrosion rate of Fe–Mo–W and Fe–Mo(W) alloys is decreased with an increase in the pH of the solutions and with the enrichment of the alloys by doping refractory components. The dependence of the control of corrosion process on the composition of electrolytic alloys has been specified. It was established that the corrosion resistance of binary alloys is 1.1 to 1.5 orders of magnitude higher in comparison with the parameters of substrate materials, in particular the mild steel. The corrosion resistance indices for the coatings applied using the ternary Fe–Mo–W alloys substantially prevail over those for mild steel, individual metals and binary Fe–Mo and Fe–W coatings. The corrosion resistance of Fe–Mo–W system is equal to 8300 Ohm·cm² and it is conditioned by the formation of the two-component layer film consisting of molybdenum oxides and tungsten oxides. Using the data of gravimetric investigations we constructed the diagrams "the corrosion depth index kh, mm/year – the composition" for the Fe–Mo–W system that allow us to define the metal content ratio for Fe–Mo(W), Fe–Mo–W alloys in order to provide an appropriate corrosion resistance depending on service conditions.

Методами аналізу поляризаційних залежностей, спектроскопії електродного імпедансу та гравіметрії досліджені корозійні властивості гальванічних бінарних Fe-Mo (або W) і тернарного Fe–Mo–W покриттів у середовищах різної кислотності. Показано, що швидкість корозії Fe–Mo–W і Fe–Mo (або W) сплавів зменшується у напрямку зростання pH розчинів, а також зі збагаченням сплавів легуючими тугоплавкими компонентами. Визначено залежність контролю корозійного процесу від складу електролітичних сплавів. Встановлено, що корозійна стійкість бінарних сплавів на 1,1-1,5 порядки величини вища за параметри матеріалу підкладки і низьковуглецевої сталі. За показниками корозійної стійкості покриття сплавами Fe–Mo–W суттєво переважають низьковуглецеву сталь, індивідуальні метали та бінарні Fe–Mo і Fe–W покриття. Опір корозії сплаву Fe–Mo–W становить 8300 Ом, що обумовлено формуванням на поверхні покриття шарів плівки оксидів молібдену та вольфраму. За результатами гравіметрічних досліджень побудовано діаграми "склад – глибинний показник корозії kh, мм/рік" для системи Fe–Mo–W, які дозволяють визначити співвідношення вмісту металів у Fe–Mo(W), Fe–Mo–W сплавах для реалізації необхідної корозійної стійкості залежно від умов експлуатації.
Корозійні властивості гальванічних Fe–Mo(W), Fe–Mo–W покриттів
Keywords: iron; molybdenum; tungsten; electrodeposition; corrosion resistance